PENGARUH GCG, STRUKTUR KEPEMILIKAN, MODAL INTELEKTUAL, DAN FINANCIAL LEVERAGE TERHADAP KINERJA KEUANGAN - Phan William, Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2020)
This study aims to analyze the influence of good corporate governance, ownership structure, intellectual capital and financial leverage on financial performance. This research used purposive sampling method. The type of data is panel data during 2016-2018 from the Stock Exchange The Indonesian effect with total sample 189 data. Data analysis techniques using multiple linear regression with Eviews 10. The results indicate that good corporate governance, managerial ownership and institutional ownership have no significant effect on financial performance, but intellectual capital and financial leverage have an effect significant impact on financial performance.